(untitled) (Itinera, 2023)
This paper aims at investigating the intertwining between dance and architecture by taking as a case study the dance of Anna Halprin (1920-2021), whose character of rupture with modern dance contributes to the questioning of dance codes and conventions that essentially informs western contemporary dance. After a presentation of Anna’s intention to strengthen dance’s function of transforming people’s lives by restoring the original link between dance and nature, we will show how this intention leverages the ritual, essentially performative dimension of dancing. After underlining, with Alberto Pérez-Gómez, the original link between architecture and ritual understood as an action of displaying – rather than imposing – a pre-existing meaning and opening up to its unfolding, we will emphasise how the outdoor dance studio built for Anna by her husband, the urban architect and landscape planner Lawrence Halprin (1916-2009), invites to take up this action. The notion of lived corporeity developed by Hermann Schmitz in his “New Phenomenology” (1965), and that of “atmospheric affordances” (Griffero 2013), will allow us to show that dancing on this studio triggers an “exploratory” attitude of unprecedented ways of moving and interacting with one’s own surroundings by virtue of the everchanging interaction between architectural, meteorological and natural elements provided by this space. Finally, the conception of “material performativity” (Dalmasso 2020) will bring out that the transformative capacity of dance derives precisely from its ability to grasp and differentially decline the performative process of mutual constitution and influence between human and non-human entities.